2015
DOI: 10.1097/dss.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic and Functional Outcomes of 2-Stage Versus 3-Stage Paramedian Forehead Flap Techniques

Abstract: Therapy, Level III, and retrospective comparative study with prospectively collected data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Aesthetic results of 3-stage forehead flap technique; in terms of flap thickness compared with the 2-stage technique was not found superior. The 2-stage technique was considered state-of-the-art choice for nasal reconstruction even in complex nasal defects 17 .…”
Section: S173mentioning
confidence: 99%
See 1 more Smart Citation
“…Aesthetic results of 3-stage forehead flap technique; in terms of flap thickness compared with the 2-stage technique was not found superior. The 2-stage technique was considered state-of-the-art choice for nasal reconstruction even in complex nasal defects 17 .…”
Section: S173mentioning
confidence: 99%
“…Stahl et al, in a prospective study of 9 years documented nosuperior aesthetic outcomes in comparison of 3-stage forehead flap technique, especially in relation to flap thickness compared with the 2stage technique. They considered 2-stage technique as better choice for nasal reconstruction, even in complex defects 17 .…”
Section: S173mentioning
confidence: 99%
“…Several small comparative studies have attempted to objectively compare the aesthetic outcomes of 2- and 3-stage paramedian forehead flaps. 7 , 18 , 19 In 2012, Ribuffo et al utilized a visual analog scale (scored 1–10) to assess aesthetic and functional outcomes of 2- versus 3-stage flaps. Assessing flap thickness, the authors found that 3-stage flaps were significantly thinner at the nasal tip (1.62 versus 3.26 mm), dorsum (1.84 versus 3.63 mm), and sidewall (1.86 versus 3.6 mm).…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that the additional surgical procedure may lead to increased risk of fibrosis at the nasal ala, which could contribute to differential thickness and satisfaction rates. 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation